Pelatihan dan Workshop “Yuk Beli Saham Syariah, miliki Indonesia” Sebagai Upaya Meningkatkan Literasi Keuangan Syariah Generasi Muda DKI Jakarta - Ahmad Maulidizen; Sujoko Winanto; Danang Indrajaya; Abdul Haris Muchtar; Amriatus Safa’ah; Muhammad Rafiq Thoriq (Society : Jurnal Pengabdian Masyarakat, 2022)
This Digital Public Education Event is a series of events from the ESQ Business School Sharia Investment Gallery External Division Work Program. The theme raised was "Yuk Beli Saham, Miliki Indonesia", containing knowledge sharing on investment and the Islamic capital market, technical deepening regarding how to start investing correctly and adequately during a pandemic and how to open an investment account with the support of PT. Indo Premier. Securities. This event was held in November in conjunction with Heroes' Day to raise public awareness to help the country deal with the economic recession. With this event, it is hoped that the spirit and soul of the heroes will become a driving force in helping the country deal with the pandemic's impact on all aspects of life. This event is held online through the Zoom application, presented directly by the presenter, which includes an introduction and initial steps in investing. The expected output is that the participants correctly understand the investment and the capital market. After the event, participants can start opening an investment account at the ESQ Business School Sharia Investment Gallery, which is then directed to follow further education so that they can carry out investment practices properly and correctly. The activity result measure with the survey was carried out, which was distributed via google form to assess the material's content and the presenters' quality. A total of 220 participants and 186 people who filled out respondents with average results were satisfied with the material presented. Suggestions based on this activity are the need for more intense assistance for participants in investing in shares on the Indonesia Stock Exchange so that they can obtain optimal profits